Reducing Misconception of Force Concepts Through Learning Conceptual Change Model with Cognitive Conflict Approach - Muh. Makhrus; Ahmad Busyairi (Department of Physics Education, Universitas Mataram, 2022)
This type of research is quantitative research that aims to reduce students' misconceptions through learning a conceptual change model with a cognitive conflict approach (CCM-CCA). The population in this study were students of the Physics Education Study Program, the University of Mataram, and students of the Surabaya State University Science Education Study Program. The sample in this study amounted to 56 second-semester students at both universities, each of which amounted to 29 people. The CCM-CCA used has been validated in Focus Group Discussion (FGD) activities and has been declared valid in content and construct so that it is appropriate to use. Data in this study were obtained through misconceptions tests, observations of conceptual changes and cognitive conflicts, and the interview process. Data analysis in this study used descriptive analysis by looking at the comparison of the percentage of students who had misconceptions before and after being given treatment and analyzing the level of cognitive conflict. The results of this study indicate that the CCM-CCA learning model is effective in reducing student misconceptions. Conceptual changes and cognitive conflicts that occur in students are included in the high and very high categories, and the results of structured interviews show that students experience 4 thought processes while learning CCM-CCA which helps students to change their conceptions from initially experiencing misconceptions to understanding scientific concepts.